2022
DOI: 10.3389/fonc.2021.657512
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Transarterial Chemoembolization Combined With Immune Checkpoint Inhibitors and Tyrosine Kinase Inhibitors for Hepatocellular Carcinoma

Abstract: PurposeTo explore the safety and efficacy of transarterial chemoembolization (TACE) in combination with immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) for the treatment of unresectable hepatocellular carcinoma (uHCC).Materials and MethodsFrom August 2019 to July 2020, patients who received TACE combined with ICIs and TKIs were retrospectively analyzed. Treatment-related adverse events (AEs) were recorded. The Kaplan–Meier method was used to estimate time to progression (TTP) and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
3
16
1
Order By: Relevance
“…PFS at 0.5, 1, 1.5, and 2 years were evaluated in 13 ( 21 , 25 , 31 38 , 40 42 ), 13 ( 21 , 25 , 31 38 , 40 42 ), 11 ( 21 , 25 , 31 37 , 41 , 42 ), and 5 studies ( 21 , 32 , 34 , 37 , 42 ), and the pooled rates and 95%CI were 0.781 (0.688-0.862), 0.387 (0.293-0.486), 0.117 (0.076-0.165), and 0.069 (0.005-0.182), respectively ( Table 3 ). OS at 0.5, 1, 1.5, 2, and 3 years were evaluated in 12 ( 21 , 25 , 31 36 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 9 ( 21 , 31 34 , 39 42 ), and 5 studies ( 21 , 31 33 , 42 ), and the pooled rates and 95%CI were 0.943 (0.902-0.975), 0.690 (0.585-0.786), 0.385 (0.246-0.533), 0.212 (0.117-0.324), and 0.056 (0.028-0.091), respectively ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PFS at 0.5, 1, 1.5, and 2 years were evaluated in 13 ( 21 , 25 , 31 38 , 40 42 ), 13 ( 21 , 25 , 31 38 , 40 42 ), 11 ( 21 , 25 , 31 37 , 41 , 42 ), and 5 studies ( 21 , 32 , 34 , 37 , 42 ), and the pooled rates and 95%CI were 0.781 (0.688-0.862), 0.387 (0.293-0.486), 0.117 (0.076-0.165), and 0.069 (0.005-0.182), respectively ( Table 3 ). OS at 0.5, 1, 1.5, 2, and 3 years were evaluated in 12 ( 21 , 25 , 31 36 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 9 ( 21 , 31 34 , 39 42 ), and 5 studies ( 21 , 31 33 , 42 ), and the pooled rates and 95%CI were 0.943 (0.902-0.975), 0.690 (0.585-0.786), 0.385 (0.246-0.533), 0.212 (0.117-0.324), and 0.056 (0.028-0.091), respectively ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…TACE was adopted in 10 studies ( 21 , 30 33 , 38 42 ), and HAIC were in 5 studies ( 25 , 34 37 ), respectively. Table 4 exhibited the outcomes using TACE+TKIs+ICIs and HAIC+TKIs+ICIs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al have found that metformin triggers the NF-κB signal pathway, which leads to caspase-3/GSDME-mediated cancer cell death [48]. Many recent attempts to increase effectiveness by combining TACE and targeted treatment with immunotherapy have been documented [49][50][51][52]. As a local chemotherapy modality, TACE can promote better immunotherapy by modulating the TIME [50].…”
Section: Discussionmentioning
confidence: 99%
“…N e v e r t h e l e s s , m o n o t h e r a p i e s w i t h e i t h e r immunotherapeutic agents alone or molecularly targeted drugs alone are not entirely satisfactory (6) (8), which induces a large number of T cells to migrate to the lesion site. This results in high expression of PD-1 molecules on the surface of the T cells, providing more targets for PD-1 inhibitors (30,31).…”
Section: Casementioning
confidence: 99%
“…These combinations have improved the objective response rate of advanced HCC. It may also be possible to increase the efficacy of immunotherapeutic agents synergistically by first performing transarterial chemoembolization (TACE) (7), which can induce the release of large amounts of tumor antigens (8). This may improve patient outcomes and prognosis.…”
Section: Introductionmentioning
confidence: 99%